Rituximab Responsive Relapsing–Remitting IgG4 Anticontactin 1 Chronic Inflammatory Demyelinating Polyradiculoneuropathy Associated With Membranous Nephropathy: A Case Description and Brief Review. Issue 4 (June 2022) - Remiche, Gauthier; Monteiro, Marta Lamartine S.; Catalano, Concetta; Hougardy, Jean-Michel; Delmont, Emilien; Boucraut, José; Mavroudakis, Nicolas
Abstract: Nodal/paranodal IgG4-related chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) rarely involves anticontactin (CNTN1) subtype and exceptionally complicates with nephrotic syndrome. A 65-year-old man developed weakness, facial palsy, and balance impairment; after spontaneous recovery, he severely relapsed 1 month later. Electroneuromyography confirmed CIDP. Proteinorachy (462 mg/dL; N < 45), proteinuria (3.5 g/g creatine), and biopsy-proven membranous nephropathy were identified. Intravenous immunoglobulins, corticosteroids, and plasmaphereses did not allow recovery. Anti-CNTN1 immunoglobulin G4 (IgG4) assay was positive. Rituximab (375 mg/m 2 /week, 4 weeks) provided obvious improvement. Relapsing–remitting anti–CNTN1-CIDP co-occurring with nephrotic syndrome is exceptional, and its identification is essential because efficient therapies such as rituximab are available for this severe condition.